2019
DOI: 10.1186/s13046-019-1160-9
|View full text |Cite
|
Sign up to set email alerts
|

Valproic acid exhibits anti-tumor activity selectively against EGFR/ErbB2/ErbB3-coexpressing pancreatic cancer via induction of ErbB family members-targeting microRNAs

Abstract: Background Deregulated ErbB signaling plays an important role in tumorigenesis of pancreatic cancer. However, patients with pancreatic cancer benefit little from current existed therapies targeting the ErbB signaling. Here, we explore the potential anti-tumor activity of Valproic acid against pancreatic cancer via targeting ErbB family members. Methods Cell viability assay and apoptosis evaluation were carried out to determine the efficacy of VPA on pancreatic cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Some other studies showed that valproic acid, a fatty acid derivative, was efficient in ex vivo expansion of other types of stem cells, such as haematopoietic stem cells from umbilical cord blood [54] and placenta-derived mesenchymal/stromal stem cells [55]. Otherwise, it is an important FDA-approved drug component with several beneficial effects and of great interest for the treatment of different types of cancers [56]. As a medication, it is mostly used to treat seizure disorders, mental/mood conditions, such as manic phase of bipolar disorder [57], and to prevent migraine headaches [58].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies showed that valproic acid, a fatty acid derivative, was efficient in ex vivo expansion of other types of stem cells, such as haematopoietic stem cells from umbilical cord blood [54] and placenta-derived mesenchymal/stromal stem cells [55]. Otherwise, it is an important FDA-approved drug component with several beneficial effects and of great interest for the treatment of different types of cancers [56]. As a medication, it is mostly used to treat seizure disorders, mental/mood conditions, such as manic phase of bipolar disorder [57], and to prevent migraine headaches [58].…”
Section: Discussionmentioning
confidence: 99%
“…ERBB2, commonly referred to as HER2, may be critical for enhancing the synergistic effect of PI3K inhibitors in HNSC patients (Michmerhuizen et al, 2019). It is generally believed that dysregulated ERBB2 signaling plays a key role in the development of pancreatic cancer (Lin et al, 2019). For the treatment of intestinal adenocarcinoma, ERBB2 mutations and amplification in small intestinal adenocarcinoma patients also make a great contribution (Adam et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated miRNA changes in animal models or patients with different conditions, which reveals the potential for miRNAs to serve as novel biomarkers for the diagnosis or treatment of epilepsy, cancer, and other human diseases [ 36 - 38 ]. AEDs such as VPA can exert anticancer and neuroprotective actions by regulating miRNA levels [ 39 , 40 ].…”
Section: The Epigenetic Effects Of Antiepileptic Drugsmentioning
confidence: 99%
“…discovered that brivaracetam and lacosamide regulate the expression of miRNAs in glioma cells; in particular, the regulation of miR-195-5p seems to affect the cell cycle, while the regulation of miR-107 seems to be involved in the inhibition of cell migration; therefore, these two drugs also have the potential to be an adjuvant treatment for glioma [ 71 ]. A recent study demonstrated that the VPA-induced simultaneous downregulation of EGFR, ErbB2, and ErbB3 in pancreatic cancer cells could slow the progression of pancreatic cancer, which was mainly attributed to the induction of ErbB family member-targeting miRNAs [ 40 ]. Moreover, recent evidence has shown that miR-145-5p upregulation in thymoma cells mediated by VPA exhibits antitumour effects as well as better responsiveness to chemotherapy [ 72 ].…”
Section: Application Of the Epigenetic Effect Of Antiepileptic Drugsmentioning
confidence: 99%